Financial Sustainability and Firm Performance Impact on Stock Prices: An Evidence from an Emerging Economy - Sarah Qaim; BushraZulfiqar; Dr. Akmal Shahzad; Dr. Taseer Salahuddin (Elementary Education Online, 2023)
This study was conducted with the purpose to see the impact of financial sustainability and firm performance on stock prices. Financial sustainability covering the long term and firm performance covering the short term performance of a firm. Sample taken for the study was the manufacturing industry of Pakistan which has 25 sectors and within all the sectors there are 379 firms. Data was collected on annual basis from 2010 to 2019. Financial sustainability was determined by Sustainable Growth Rate (SGR) and firm performance was calculated through Return on Assets (ROA) whereas firm size and firm age was taken as control variables. Regression was used to see the significance of the impact of financial sustainability and firm performance on stock prices. According to the results, both long term and short term performance has a significantly positive impact on the stock prices of a firm, which shows that operations of a firm, whether short term or long term do have an important role to play. This study also enhances the importance of financial sustainability for a firm. This study can be helpful for the policy makers and investors as well.